(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article is devoted to the issue of women’s rights when entering into marriage, as well as the cultural and moral foundations for resolving the women’s issue in Islamic law. The author examines the content of the concept of women’s rights in Islam by citing substantiated facts from the Koran and hadiths. Spiritual values play the most important role in the spiritual healing of society and the strengthening of the family. But if religious norms and rules are interpreted incorrectly, then they can become the basis for discrimination against women. Such attempts, on the one hand, lead to the infringement of women’s rights, and, on the other hand, they cast a shadow on Islam.’s rights, code , Koran, Hadith.